Pengaruh Indeks Pembangunan Gender, Tingkat Kemiskinan dan Pengeluaran Per Kapita Terhadap Indeks Pembangunan Manusia dalam Perspektif Ekonomi Islam Di Provinsi Banten Periode Tahun 2013 -2020 - Syifa Fauziyyah; Naf’an Tarihoran; Dedi Sunardi (Jurnal Simki Economic, 2022)
This study aims to determine the effect of Gender Development Index, poverty rate and per capita expenditure against Human Development Index for the periode 2013 – 2020. Human development as the goal of economic development to improve the quality and welfare of people’s lives. HDI measures the achievement of socio – economic development is reflected in the gender equality, prevention poverty av nd prosperity. The research method used is a quantitative method. Using secondary data obtained from BPS Banten Province. Data analysis used multiple linear regression analysis technique by fulfilling the classical assumption test with SPSS 23. The results showed that GDI had no significant effect on HDI. The relevance of GDI with HDI as a measure of development achievement, but GDI is not a factor that affect HDI. Poverty rate has a significant effect on HDI, because poverty is the cause of the disparity behind the low quality and productivity of the community. Per capita expenditure has a significant effect on HDI, because it is an indicator of measuring economic walfare. The variable of GDI, poverty rate, and per capita expenditure have a simultaneous effect on HDI and have an effect of 95,6 %. Gender in Islamic Economics guarantees the principle of equality. Poverty is the inability to meet material and spiritual needs. Per capita expenditure, namely economic activity based on the concept of islamic man and falah oriented. Human development as a sustainable comprehensive effort to improve well being.